Relationship Between Problem-Focused Coping and Social Support with Life Meaning in Female Sex Workers - Putra, Bagas Mahendra; Noviekayati, IGAA; Santi, Dyan Evita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The profession of being a female sex worker carries various forms of risks that encompass physical, sexual, and social aspects. Engaging in this work over a long period is a process filled with courage, self-reflection, and complex dynamics of changing life perspectives. Nevertheless, many of them still have hopes and determination to improve their lives for the better. This study focuses on efforts to understand the relationship between problem-focused coping and social support with life meaningfulness among female sex workers. The research approach used is quantitative with a multiple correlation analysis model. From a total population of 232 people, 44 respondents were selected as the research sample. The research instruments included measures of problem-focused coping, social support, and life meaningfulness, which were analyzed using multiple correlation techniques. The results showed that the first hypothesis could not be tested because the data did not meet the normality assumption. Meanwhile, the second hypothesis indicated a negative relationship between problem-focused coping and life meaningfulness, whereas the third hypothesis found a positive relationship between social support and life meaningfulness. These findings suggest that the greater the social support received, the higher the level of life meaningfulness experienced by female sex workers.